Penerapan Kurikulum Merdeka Belajar Dalam Meningkatkan Minat Mahasiswa Dalam Pembelajaran Bahasa Arab Di UIN Mataram - Halimatus Sa’adiah; Suparmanto, Suparmanto; Rizki Umar, Azidan; Hasanah, Pajriatul; Bidaini, Bidaini (Tanfidziya: Journal of Arabic Education, 2024)
Arabic language subjects are subjects that are considered important by the Ministry of Religion considering that the majority of Indonesian people are Muslim. Arabic is one of the mandatory subjects in the curriculum for schools under the auspices of the Ministry of Religion. Therefore, studying Arabic and teaching it in various educational institutions in Indonesia continues to maintain its existence. Many phenomena in Arabic language teaching found in the field show students' difficulties in making sentences in Arabic. This is partly due to monotonous learning, which causes students to lack interest and motivation in learning Arabic. This research aims to evaluate the role of the Independent Curriculum in increasing students' interest in learning Arabic at the Mataram State Islamic University. This research was conducted on November 27 of the 2023/2024 academic year involving all class A students of the Arabic Language Education Study Program, Mataram State Islamic University. The results obtained show that the Merdeka Curriculum can increase students' interest in learning.